Religious Spaces and Biodiversity in Contemporary Myanmar - Anders Blomso; Cheryl Swift; Christina Mecklenburg; Jason Carbine; Julia Davis; Marissa Ochoa; Rosemary P. Carbine (The ASIANetwork Exchange: A Journal for Asian Studies in the Liberal Arts, 2020)
Drawing together methodologies and analytical frameworks from religious studies and environmental science and related fields, this paper discusses the possible role of Buddhist sacred spaces in conserving biodiversity in Myanmar. Faculty and students worked together to analyze relationships between sacred spaces, religious practice, and biodiversity. We explored whether there was any evidence for an emergent or present Buddhist eco-ethic in Myanmar that fused religious spaces and places with environmental protection, and if so, how it might resonate with Buddhist environmentalism in other areas of the world, such as in Thailand, in the Tibetan regions of China, and elsewhere.1